Caracterización de valores hemáticos (biometría hemática) en individuos derivados del cruce entre las especies lama Glama y lama Pacos (guarizo) - Jácome Melo, Juan Carlos (2016)
This investigation had as objective it establishes values haematológical of our means and to determine the variation of recount leucocytes and erythrocytes as well as the index erythrocytes between two groups of ages of 2 to 4 years and of 4 at 6 the group of smaller age presents bigger values in it formulates it red and it formulates it white the same as it formulates it plaquetaria. The study was carried out since with a sample of 30 animals of an entirety of 112 the sample it was inside the parameters of ages similar corporal and characteristic conditions inside the sample in an atmosphere controlled after having carried out a clinical test and the experimental units were seemingly healthy you standardizes the values haematológical of the species guarizo, in this investigation it is necessary to stand out the conditions in those that it was elaborated this investigation like altitude 3.267 msnm. In the county of Cotopaxi....